Role of cytochrome b5 in the modulation of the enzymatic activities of cytochrome P450 17α-hydroxylase/17, 20-lyase (P450 17A1). Issue 170 (June 2017) - Bhatt, Megh Raj; Khatri, Yogan; Rodgers, Raymond J.; Martin, Lisandra L.
Graphical abstract: Highlights: Cytochrome b5 (cyt b5) as a regulator of P450 17A1 enzyme activity is reviewed. Cyt b5 is critical for switching on androgens vs. cortisols and hence is a potential drug target for reduction of androgens. The molecular and biochemical perspective of cyt b5 in P450 17A1 catalysis is included. The role of cyt b5 in the modulation of P450 17A1 activity is described. The electronic connection between cyt b5 and P450 17A1 has been published but the mechanistic stages remain unknown. Abstract: Cytochrome b5 (cyt b5) is a small hemoprotein that plays a significant role in the modulation of activities of an important steroidogenic enzyme, cytochrome P450 17α-hydroxylase/17, 20-lyase (P450 17A1, CYP17A1). Located in the zona fasciculata and zona reticularis of the adrenal cortex and in the gonads, P450 17A1 catalyzes two different reactions in the steroidogenic pathway; the 17α-hydroxylation and 17, 20-lyase, in the endoplasmic reticulum of these respective tissues. The activities of P450 17A1 are regulated by cyt b5 that enhances the 17, 20-lyase reaction by promoting the coupling of P450 17A1 and cytochrome P450 reductase (CPR), allosterically. Cyt b5 can also act as an electron donor to enhance the 16-ene-synthase activity of human P450 17A1. In this review, we discuss the many roles of cyt b5 and focus on the modulation of CYP17A1 activities by cyt b5 and the mechanisms involved.